José María Zamora Calvo. Éticas estoicas. Madrid: Tecnos, 2023; 344 pp., ISBN: 978-84-309-8926-3 - Manon Ertola Urtubey (Synthesis (La Plata))
Reseña de Éticas estoicas de J. M. Zamora Calvo por M. Ertola Urtubey.